2015
DOI: 10.17102/cnr.2015.03
|View full text |Cite
|
Sign up to set email alerts
|

Diversity, Occupancy, and Spatio - temporal Occurrences of Mammalian Predators in Bhutan's Jigme Dorji National Park

Abstract: The Gaur, Bos gaurus Smith, plays an important role in the pyramidal food chain -being an important prey for large carnivores such as tiger, common leopard, and Asiatic wild dog. Presence of Gaur in an area indicates wild and healthy ecosystem. Reduction of global distribution of Gaur by over 80% in the past 100 years, scaling in the IUCN Red List of Vulnerable category shows the species is facing serious threats. The present study assessed the distribution, activity pattern, and abundance of Gaur in the Royal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 0 publications
2
21
0
Order By: Relevance
“…The highest number of Dhole evidence (n = 426) were recorded from CBLF and the least from CF (n = 2). A similar pattern was also observed by Thinley et al (2015a) in the same park during a camera trap survey in 2012. There was a highly significant difference in the number of Dhole evidence among the vegetation types (Kruskal-Wallis chi-squared = 33.8249, df = 6, p < 0.005).…”
Section: Dhole Habitat Usesupporting
confidence: 82%
See 2 more Smart Citations
“…The highest number of Dhole evidence (n = 426) were recorded from CBLF and the least from CF (n = 2). A similar pattern was also observed by Thinley et al (2015a) in the same park during a camera trap survey in 2012. There was a highly significant difference in the number of Dhole evidence among the vegetation types (Kruskal-Wallis chi-squared = 33.8249, df = 6, p < 0.005).…”
Section: Dhole Habitat Usesupporting
confidence: 82%
“…So far, seven cat species -including the Tiger and Snow Leopard Panthera uncia, and four canid species -including the Gray Wolf Canis lupus, Red Fox Vulpes vulpes, and Asiatic Jackal Canis aureus, have been recorded in the park (Thinley et al 2015a). Seven species of ungulates have also been recorded -including the endemic Bhutan Takin Budorcas taxicolor whitei, the endangered Himalayan Musk Deer Moschus leucogaster, and the endangered Alpine Musk Deer Moschus…”
Section: Study Area Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This information may suggest that their abundance, relative to other species, likely varies significantly across their range in South Asia (McCarthy et al 2015) and warrants further investigation. Increasing camera-trap surveys in Bhutan are recording further detection of the species (Jigme 2011;Tempa et al 2011Tempa et al , 2013Thinley et al 2015b). The Asiatic Golden Cat has been recorded from the southern foothills of Royal Manas National Park at elevations of 80m (Tempa et al 2011(Tempa et al , 2013 to Jigme Dorji National Park at an elevation of 4033m (Jigme 2011) (Table 1) (Jigme 2011;Tempa et al 2011Tempa et al , 2013DoFPS 2015), and two districts outside of the protected areas: Trongsa and Wangdue Phodrang (Jigme 2011).…”
Section: Distributionmentioning
confidence: 99%
“…Recent records have reported their presence in areas of dwarf rhododendron forest and grasslands at high elevations (Wang 2007), in conifer forests dominated by Fir Tsuga dumosa (Vernes et al 2015), and also in cool broadleaf and mixed-conifer forests (Thinley et al 2015b). Tempa et al (2013) reported the species from Royal Manas National Park where the vegetation is mainly dominated by warm broad-leaved forests.…”
Section: Habitatsmentioning
confidence: 99%